The Twists and Turns of Diagnosis and Treatment of Pediatric Neuro-Behcet's Disease: A Case Report and Literature Review - Zhang, Qiao; Luo, Yizhen; Zhou, Jianli; Zhou, Shaoming; Wang, Zhaoxia (Frontiers in Pediatrics, 2021)
Neurological manifestations in a patient with Behcet’s disease (BD) led to the identification of Neuro-Behcet’s disease (NBD). As there is no specific diagnostic test, the diagnosis and management of NBD is challenging. We report a 11-year and 11-month boy who underwent right eye intraocular lens implantation, appendectomy, perianal abscess removal, thalidomide therapy and infusions of infliximab for his Crohn disease (CD). Magnetic resonance imaging (MRI) and magnetic resonance venography (MRV) were performed to address the onset of headache during the course of his treatment which showed Cerebral Venous Sinus Thrombosis (CVST). After the diagnosis of NBD, he was treated with anticoagulation (nadroparin calcium), and low-dose corticosteroids combined with immunosuppressant (cyclophosphamide), leading to his recovery. Here, we describe how NBD is prone to misdiagnosis and missed diagnosis, and should be diagnosed based on the clinical manifestations, colonoscopy, pathological examination and MRI or MRV.